KRAS mutation profile differences between rectosigmoid localized adenocarcinomas and colon adenocarcinomas - Baskin, Yasemin (Pioneer Bioscience Publishing Company, 2014)
BACKGROUND: Colorectal cancer has a heterogeneous nature that is influenced by the tumour site. Many improvements have been made in identifying and characterizing the genetic alterations between colon and rectal cancers. However, there is not enough information about KRAS mutational differences between rectosigmoid and colon cancers arising elsewhere in the large bowel. The aim of this study was to determine the differences in the frequency of KRAS genetic alterations between rectosigmoid cancers and colon cancers. METHODS: Eighty-four patients diagnosed with colorectal cancer were included in this study. Genomic DNA was extracted from formalin-fixed paraffin-embedded tumour tissue sections. KRAS mutation analysis which was designed to detect the seven most common KRAS gene mutations (Gly12Ala, Gly12Asp, Gly12Arg, Gly12Cys, Gly12Ser, Gly12Val and Gly13Asp) was performed. Chi-square test was used to test the association between mutation status and other variables. RESULTS: This study represents the first KRAS mutational results from Turkish rectosigmoid cancer patients. The KRAS mutation frequency of rectosigmoid tumours is higher (34.3%, 12/35) than that of colon-localized tumours (30.6%, 15/49). However, there is no significant correlation between the KRAS mutation status and tumour location (rectosigmoid and colon). CONCLUSIONS: KRAS mutation analysis has a predictive and prognostic value in identifying tumours that may be resistant to treatment. Our study shows that differences in the biological behaviour of rectosigmoid and colon cancers should be considered. This finding highlights the importance of personalized cancer management, which could be assisted by cancer genotyping tools.